THE ANALYSIS OF HOSPITALIZATION IN MASSIVE ADMISSIONS OF VICTIMS TO N.V. SKLIFOSOVSKY RESEARCH INSTITUTE FOR EMERGENCY MEDICINE - M. S. Khubutiya; S. V. Stolyarov; N. A. Karasev; E. V. Kislukhina; B. L. Kurilin; I. V. Kiselev (Неотложная медицинская помощь, 2017)
N.V. Sklifosovsky Research Institute for Emergency Medicine is the main clinical base for medical elimination of mass disasters consequences, and about 20% of victims arrive here in emergency situations in Moscow. The current clinical structure of N.V. Sklifosovsky Research Institute for Emergency Medicine provides for the provision of skilled medical care to a large number of patients in massive admissions. Resuscitation departments of various specialties are organized at the Institute. In elimination of medical consequences of mass disasters, 11 clinical departments with 544 beds and 9 resuscitation departments are used. The capacity of resuscitation units (101 beds) allows to admit a large number of severely affected patients simultaneousely, including patients with combined and multisystem trauma, as well as to re-admit after surgery, taking into account the type of injury.